1999
DOI: 10.1086/306995
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Novae, Event Horizons, and the Exponential Metric

Abstract: Magnetic Eternally Collapsing Objects (MECO) have been proposed as the central engines of galactic black hole candidates (GBHC) and supermassive active galactic nuclei (AGN). Previous work has shown that their luminosities and spectral and timing characteristics are in good agreement with observations. These features and the formation of jets are generated primarily by the interactions of accretion disks with an intrinsically magnetic central MECO. The interaction of accretion disks with the anchored magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…One should mention that if the space-time geometry is described by the exponential metric then compact supermassive objects at galactic centers can not be made of baryonic matter. Maximum mass of a compact (neutron star like) baryonic object in such a metric can not exceed about 12M ⊙ [27]. Hence, dark matter of non baryonic origin is the only alternative for their composition.…”
Section: Discussionmentioning
confidence: 99%
“…One should mention that if the space-time geometry is described by the exponential metric then compact supermassive objects at galactic centers can not be made of baryonic matter. Maximum mass of a compact (neutron star like) baryonic object in such a metric can not exceed about 12M ⊙ [27]. Hence, dark matter of non baryonic origin is the only alternative for their composition.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been found that the quantized theory is finite. Incidentally in the exponential metric fields approached in this work just as in the Yilmaz theory there are no black holes in the sense of event horizons, but there can be stellar collapse (Robertson 1999a(Robertson , 1999b. However, there are no point singularities.…”
Section: Resultsmentioning
confidence: 76%
“…In this approach the metric field can be characterized by a background spacetime conformally flat affected by a disturbance. We have approached some examples in this tensorial structure that results in exponential metric fields, we can point out as the main exponential metric obtained in this paper which has been extensively explored: the Yilmaz exponential metric (Yilmaz 1958(Yilmaz , 1992(Yilmaz , 1976(Yilmaz , 1982(Yilmaz , 1973(Yilmaz , 1977(Yilmaz , 1997Clapp 1973;Robertson 1999aRobertson , 1999bIbison 2006). H. Yilmaz has argued that in his theory, the gravitational field can be quantized via Feynman's method (Yilmaz 1995;Alley 1995).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Citing this property and assuming the Yilmaz theory is correct, Clapp [10] has suggested that a significant component of quasar red-shift may be gravitational. Robertson [11,12] has suggested that some Neutron stars and Black Hole Candidates may be such 'Yilmaz stars'.…”
Section: Introductionmentioning
confidence: 99%